A Lifetime of Canadian-Cuban Solidarity - Elizabeth, Hill (Canadian Woman Studies/les cahiers de la femme, 2025)
I have been involved in the Canadian-Cuban Friendship Association Toronto (CCFA Toronto) since its beginning in 1977 and have travelled to Cuba numerous times on delegations, brigades, and holidays, seeing for myself the accomplishments of the Cuban Revolution and its positive results for women in particular.